Dickkopf Homolog 3 (DKK3) Acts as a Potential Tumor Suppressor in Gallbladder Cancer - Gondkar, Kirti; Patel, Krishna; Patil Okaly, Geeta V.; Nair, Bipin; Pandey, Akhilesh; Gowda, Harsha; Kumar, Prashant (Frontiers in Oncology, 2019)
Gallbladder cancer (GBC) is a common malignancy of biliary tract cancers and its incidence has been rising rapidly worldwide. The prognosis for this disease is dismal as most of the symptoms are non-specific leading to a definitive diagnosis only at a late stage. Loss of DKK3 gene is associated with a possible tumor suppressor role in human cancers. The role and regulation of DKK3 in GBC have not been studied. We found that DKK3 expression levels were low in GBC patients and cell lines. Treatment of GBC cell lines with demethylating agent 5-Aza- 2’-deoxycytidine enhances its expression, establishing the impact of methylation on DKK3 expression. We observed low expression of DKK3 in gallbladder adenocarcinoma tumors and highly invasive GBC cell lines. We showed that overexpression of DKK3 can decrease cell invasion, proliferation and colony-forming ability of GBC cells. Our data thus demonstrated the DKK3 gene is a potential tumor suppressor gene in GBC and aberrant promoter methylation could be involved in its downregulation, which may play a role in the tumorigenesis and aggressiveness of GBC.